Patterns of Alcohol Use and Alcohol Use Disorders and Their Sociodemographic Correlates: Findings from a Cross sectional Study among Male Patients Attending a NIA Outpatient Department - Viadya Amol S. Kadu; Rupali D. Asutkar; Anita Sharma; R. K. N. Priyangika (Journal of Ayurveda, 2025)
Introduction: Alcohol consumption is a significant public health issue, contributing to substantial morbidity and mortality worldwide. In India, alcohol use prevalence ranges from 3.8% to 21%, predominantly affecting men. Despite estimates of alcohol use disorder (AUD) ranging from 7.1% to 14.2%, limited hospital-based studies exist in Rajasthan. This study examines alcohol consumption patterns, AUD prevalence, and their association with sociodemographic factors among male outpatients at NIA OPD. Methods: A hospital-based cross-sectional study was conducted on 1000 male outpatients aged 18 and above with a history of alcohol use. Data were collected from December 2018 to December 2020 using a pretested questionnaire, including the AUD identification test (AUDIT). Participants were selected through purposive sampling, and drinking patterns were categorized into hazardous, harmful, and dependent levels. Sociodemographic factors, drinking behaviors, and familial influences were analyzed using descriptive statistics. Results: The study found that 41.8% of participants consumed alcohol four or more times weekly, and 28.8% consumed six or more drinks daily. Stress relief and peer pressure were primary motivators, with 21% reporting a family history of substance abuse. Despite 76.7% awareness of alcohol’s adverse effects, risky drinking behaviors persisted. AUDIT analysis categorized 43.8% as hazardous drinkers, 29.2% as harmful drinkers, and 12.4% as alcohol-dependent. High-risk behaviors included memory blackouts, inability to meet responsibilities, and polysubstance use. Conclusion: The study underscores the need for targeted interventions, including routine screening, behavioral counseling, community awareness programs, and strengthened de-addiction services to mitigate AUD-related risks.